Artificial Intelligence and Machine Learning Applications in Infrastructure Security - Shanmugam, Navanithan (Journal of Research in Science and Engineering, 2026)
The fintech sector is one of the ideal targets for cybercriminals. Due to the sector's reliance on online platforms and the financial viability of fintech companies, attackers find fintech companies favorite targets. To mitigate the rising cybersecurity threat in the sector, fintech companies are increasingly incorporating artificial intelligence and machine learning models in their infrastructure security. This writing discusses the increasing cybersecurity threat in the fintech sector and explores how AI and ML are being leveraged in fintech cyber security.